A STUDY ON EMPLOYEE ENGAGEMENT IN HOSPITALS OF UDAIPUR DIVISION - Dr Devendra Shrimali, Ronak Kumari Upadhyay (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The research paper focuses upon understanding the concept ‘employee engagement’ and attempt to explore the employee engagement level in the hospital sector. The study intendsto measure the level of employee engagement and to compare the level between the government and private sector hospitals. The research uses a mixed approachwhich includes surveysto measure the employee engagement leveland observation and interview to have a deeper understanding of internal dynamics of hospitals. The findings of this study areproposed to illustrate the association between the engagement level of hospital staff and the demographic factors in government and private hospitals and compare the level of engagement in two different sectors. The results of the study are relevant to not only the hospitals but also to all the organisations that aim to improve the engagement of personnel and deliver quality service to customers.